A revision of the genus Greenea (Rubiaceae) - Tange, Christian (Thai Forest Bulletin (Botany), 2014)
The genus Greenea Wight & Arn. is revised using traditional herbarium taxonomic methods and fi eld observations; nine species are recognised. Four new species are described: G. adangensis, G. montana, G. rivularis and G. vietnamensis. Spathichlamys oblonga Fisher is transferred to Greenea and named G. schizocorolla. The two species G. oblonga Craib and G. siamensis Craib are reduced to varieties of G. corymbosa. Greenea wightiana Wight & Arn. is reduced to a synonym of G. corymbosa var. corymbosa. Greenea is distributed from Sumatra through the Malay Peninsula to S Thailand and Burma, and occurs again in N and SE Thailand, Laos, and Vietnam.